A high-throughput strategy to screen interfacial diffusion barrier materials for thermoelectric modules. Issue 7 (6th February 2019) - Gu, Ming; Bai, Shengqiang; Wu, Jiehua; Liao, Jincheng; Xia, Xugui; Liu, Ruiheng; Chen, Lidong
Abstract: Abstract : Diffusion barrier materials play an important role in both structure reliability and performance stability of thermoelectric (TE) modules. Preferred barrier materials are screened out from various candidates by comparing the interdiffusion at the barrier material/TE substrate interfaces. Traditionally, for each barrier material candidate, complicated fabrication processing of TE elements (electrode/barrier material/TE material) must be finished to obtain relative interfaces, which makes the screening costly and time consuming. In this article, using a high-throughput strategy, we developed a high-efficiency screening method of barrier materials. By cosintering the mixture of TE substrate material and various barrier material candidates simply following the TE material's sintering parameters, various microinterfaces were integrated to one single sample. This enables parallel aging and microstructure characterization of different interfaces, and preferred barrier materials can be swiftly screened out. As a result, it makes the design and optimization of TE modules much more efficient and economical.